THE IMPACT OF ZANGEZUR COPPER AND MOLYBDENUM COMBINE ACTIVITIES ON THE POLLUTION OF AGRICULTURAL LANDS AND CROPS BY TOXIC ELEMENTS (Proceedings of the YSU B: Chemical and Biological Sciences, 2019)
The aim of the study was to assess the pollution of agricultural lands and crops with some potentially toxic trace elements conditioned by the activities of Zangezur Copper and Molybdenum Combine, as well as an assessment of the risk level of the studied crops for human health. The study was implemented in 2018. It was revealed that the soils of agricultural land in the surroundings of the combine were polluted by some trace elements, in particular by copper, but the content of Cu in crops growing in this area did not exceed the maximum permissible concentrations (MPC). The exceeding of MPC was registered in case of Cd, Ni, Zn and Cr. The highest excess of toxic elements in vegetables was observed in garlic and above-ground parts of red beet, and in an apple among fruits. In this regard, it is essential to implement the soil renewal and remediation activities in the studied area, in particular, phytoremediation, which is considered to be a harmless and cost-effective approach to remove toxic pollutants.
Keywords: Zangezur Copper and Molybdenum Combine, toxic elements, pollution, agricultural land, soil, crops